2007
DOI: 10.1002/hlca.200790105
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Design and Synthesis of the First Weak Non‐Phosphate Inhibitors for IspF, an Enzyme in the Non‐Mevalonate Pathway of Isoprenoid Biosynthesis

Abstract: In this paper, we describe the structure-based design, synthesis, and biological evaluation of cytosine derivatives and analogues that inhibit IspF, an enzyme in the non-mevalonate pathway of isoprenoid biosynthesis. This pathway is responsible for the biosynthesis of the C 5 precursors to isoprenoids, isopentenyl diphosphate (IPP, 1) and dimethylallyl diphosphate (DMAPP, 2; Scheme 1). The nonmevalonate pathway is the sole source for 1 and 2 in the protozoan Plasmodium parasites. Since mammals exclusively util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…25 Various inhibitors of IspF have been reported 2527 including CDP. 26 For further validation of this HPLC-based assay, we tested inhibition of IspF by CDP.…”
Section: Resultsmentioning
confidence: 99%
“…25 Various inhibitors of IspF have been reported 2527 including CDP. 26 For further validation of this HPLC-based assay, we tested inhibition of IspF by CDP.…”
Section: Resultsmentioning
confidence: 99%
“…[16] More recently, a series of non-phosphate, cytosine-type inhibitors with IC 50 values in the micromolar range has been reported. [17] Earlier, we showed that fluorescent ligands for IspF protein can serve as a basis for a fluorescence-monitored ligand binding competition assay for inhibitor screening. [16] More recently, we developed a dynamically monitored kinetic assay that is suitable for the screening of large compound libraries (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Rationally designed IspF inhibitors incorporate the CDP moiety 14 or a cytidyl-like component 15 to bind in the rigid, well-conserved “pocket III” of the IspF active site, and a non-polar component to bind in the more flexible hydrophobic “pocket II”. 14 We reasoned that the unique methylerythritol scaffold could also drive recognition of selective IspF inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 These efforts by Diederich and colleagues to identify inhibitors underscore the challenges in targeting the highly polar active site of IspF.…”
mentioning
confidence: 99%